CATCHMENT CHARACTERISTICS AND PLANT RECRUITMENT FROM SEDIMENT IN STREAM AND MEADOW HABITATS. (20th April 2012) - Baattrup‐Pedersen, A.; Riis, T.; Larsen, S. E.
ABSTRACT Streams and rivers constitute a dense network with a large interface to the surrounding landscape and are thus highly susceptible to anthropogenic pressures related to land‐use activities in adjacent riparian and upland areas. In the present study, we investigated the influence of catchment characteristics on potential propagule and species recruitment from sediment in lowland stream ecosystems. We tested the following hypotheses: (1) catchment characteristics affect species recruitment from stream sediment in both stream and riparian habitats and (2) recruitment of species associated with undisturbed fen‐meadow habitats is higher in places with natural vegetation in the riparian zones. A large number of wetland species emerged from the stream sediment and sediment recruitment and therefore can act as an important dispersal corridor for common species in stream ecosystems. The recruited propagules were dominated by terrestrial species, but amphibious and aquatic species also appeared, particularly in the artificial stream channels. These included among others species within the genera Ranunculus sp., Callitriche sp. and Potamogeton sp. The large between‐site differences in land‐use characteristics in the riparian zones of the studied stream reaches, both locally and along upstream reaches, were not reflected in species recruitment from the stream sediments. Thus, most recruited species were common and widely distributed, and they were dominated by species with ruderal and competitive life history strategies, whereas only few species associated with fen‐meadow vegetation were recruited. From these findings, we infer not only that hydrochorous dispersal of species can be a potential efficient dispersal vector in agricultural landscapes but also that limitations can exist as to which species can be recruited. We suggest that further studies are performed to elucidate this issue further. Copyright © 2012 John Wiley & Sons, Ltd.